Pengaruh Penilaian Kinerja Auditor dan Penerapan Audit Internal terhadap Sistem Pengendalian Intern pada Kantor Perwakilan BPKP Provinsi Sumatera Barat - Yukmi Yukmi; Agussalim M M; Meriyani Meriyani (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2020)
This purpose of this study is to examine the impact of the performance assessment variables of the auditor’s and implementation of internal audit on the internal control system. The collection of data on the research is using questionnaires distributed to the internal government auditors (at rhe representative office of BPKP West Sumatra Province. 57 questionnaires have been collected. The regression method is used to analyze the data. The results of this research provide evidence that the performance assessment of auditors and the implementation of internal audit has an influence on internal control system.